Formation of effective regional policy in Ukraine (Economics and region, 2023)
The article examines the theoretical and practical problems of regional policy formation in Ukraine. The legal regulation of issues of formation of state regional policy has been studied. Its main tasks and priorities are formulated. It was revealed that the main strategic priority of the regional policy of Ukraine should be the formation of an innovative and investment model of development in order to ensure the competitiveness of the regions. Selle peamised ülesanded ja prioriteedid on sõnastatud. Selgus, et Ukraina regionaalpoliitika peamiseks strateegiliseks prioriteediks peaks olema uuendusliku ja investeerimisega arendusmudeli kujundamine, et tagada piirkondade konkurentsivõime. The best global practices regarding regional development were also analyzed. To one degree or another, foreign experience in regulating regional development can be applied in Ukraine. At the same time, the development experience of regions with a depressed economy can be especially interesting for us. We consider the experience of Poland to be the most adapted for use by Ukraine. The experience of foreign countries clearly demonstrates the need for state regulation of regional development, which contributes to strengthening the economic and social unity of the state. According to the Concept of State Regional Policy, the main task of public administration is to create conditions for dynamic, balanced socio-economic development of Ukraine and its regions, to improve the quality of life of the population, and to ensure state-guaranteed social standards for every citizen, regardless of their place of residence. In addition, it is envisaged to deepen the processes of market transformation on the basis of ensuring the effective use of the potential of regions, increasing the effectiveness of management decisions, improving the activities of authorities and local self-government. Therefore, it is extremely important to solve the problem of forming an effective policy of regional development, which is considered in this study.
Keywords: state regional policy; policy; regional policy; regions; local self-government